Deaf and hard-of-hearing patients are unsatisfied with and avoid German health care: Results from an online survey in German Sign Language - Julia Rannefeld; Julie Lorraine O'Sullivan; Adelheid Kuhlmey; Jan Cornelius Zoellick (BMC, 2023)
Abstract Background Approximately 235,000 deaf and hard of hearing (DHH) people live in Germany. Due to communication barriers, medical care for this group is difficult in many respects. Especially in the case of acute illnesses, the possibilities of communication, e.g., through sign language interpreters, are limited. This study investigates the satisfaction of DHH patients with medical care in Germany in unplanned medical consultations. The aim of this study is to provide insights into DHH patient's perception of medical care, to identify barriers and avoidance behaviours that stem from fears, miscommunication, and prior experiences. Methods We obtained data from adult DHH participants between February and April 2022 throughout Germany via an online survey in German Sign Language. The responses of N = 383 participants (65% female, M = 44 years, SD = 12.70 years) were included in statistical analyses. Outcomes were convictions of receiving help, satisfaction with healthcare provision, and avoiding healthcare visits; further variables were concerns during healthcare visits, incidences of miscommunication, and a communication score. We calculated t-tests, ANOVAs, correlations, and linear and logistic regression analyses. Results Our main findings show that (1) DHH patients were unsatisfied with provided healthcare (M = 3.88; SD = 2.34; range 0-10); (2) DHH patients reported many concerns primarily about communication and treatment aspects when visiting a doctor; and (3) 57% of participants deliberately avoided doctor visits even though they experienced symptoms. Factors such as concerns during doctor's visits (B = -0.18; 95%CI: -0.34--0.02; p = .027) or miscommunication with medical staff (B = -0.19; 95%CI: -0.33-0.06; p = .006) were associated with satisfaction with medical care, while we found almost no associations with gender and location, and only few with age and education. Conclusions Overall, our findings suggest that DHH patients are unsatisfied with provided healthcare, they deliberately avoid doctor visits, and they face various communication barriers. This study revealed several communication-related determinants of satisfaction with healthcare in DHH patients, such as incidences of miscommunication and the communication score. Communication-related barriers have high potential to be addressed in collaboration with the DHH community. To improve the medical care and the satisfaction with healthcare in DHH patients, training healthcare professionals, digital technologies, and other communication-enhancing interventions should be explored in future intervention studies.